Postcardiotomy extracorporeal membrane oxygenator: No longer a bridge to no where?. Issue 9 (27th July 2020) - Merritt‐Genore, HelenMari; Schwabe, Michael; Luksan, Abel; Ryan, Timothy; Lyden, Elizabeth; Moulton, Michael
Abstract: Background: Postcardiotomy extracorporeal membrane oxygenation (PC‐ECMO) represents a unique subset of critically ill patients, with a paucity of data regarding long‐term survival and correlated characteristics. We present a retrospective cohort of PC‐ECMO patients, with outcomes at 1 and 3 years. Methods: Data were collected retrospectively for all patients requiring ECMO within 72 hours of an index cardiac operation (excluding assist devices and transplants). Primary outcomes were the ability to wean from ECMO, hospital survival, and long‐term survival. Results: Thirty‐one patients required PC‐ECMO, representing a total of 172 days of ECMO support. Overall survival data were the ability to wean 58%, hospital survival 52%, 1‐month survival 42%. The estimated 12‐ and 36‐month survival for all PC‐ECMO patients was 35% and 29%, respectively. Twelve and 36‐month survival for all hospital survivors was 62% and 56%. Operative times, the Society of Thoracic Surgeons risk scores, type of operation, open chest status, hemorrhage, and cannulation location, and timing were all compared. Centrally cannulated patients were more likely to wean from ECMO (83% vs 44%; P = .03), and survive hospitalization (75% vs 36%; P = .04) and trended toward long‐term survival benefit (67% vs 33%; P = .06). Otherwise, no statistically significant relationships were observed. Conclusions: Central cannulation may provide benefits in the postcardiotomy patient, compared to peripheral strategies. Twelve and 36‐month survival for all PC‐ECMO patients was 35% and 29%. For hospital survivors, 12 and 36‐month survival 62% 56% at 36. These data support PC‐ECMO as a reasonable salvage strategy, with midterm survival comparable to other surgically treated diseases.